THE COASTAL CURRENT SOUTH OF JAVA - Soeriaatmadja, Raden E. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1957)
This paper concerns investigations of the hydrography of the waters south of Java, especially of the Java Coastal Current, which have been carried out by the Institute of Marine Research at Djakarta. It is based on (1) oceanographic observations made by the research vessel